Homoeopathic Management of Gastroenteritis with Nux vomica LM Potency: A Case Study - Dr Dhaval Jadhav; Dr. Rakesh Gohel (The Bioscan, 2026)
Gastroenteritis is an acute inflammatory condition of the stomach and intestines and remains a major cause of morbidity worldwide. In India, it contributes substantially to childhood illness and hospitalisation, with viral agents—particularly rotavirus—playing a dominant role. Despite improvements in vaccination coverage and sanitation, gastroenteritis outbreaks related to contaminated water and food continue to occur in several states, including Gujarat. This short review summarises the definition, epidemiology, causes, and clinical features of gastroenteritis with a focus on India and Gujarat, highlighting its public health importance. In this condition homoeopathy give marked improvement in this case with LM Potency prescription in very short time which give rapid and gentle cure to the patient. Keywords Gastroenteritis, acute diarrhoeal disease, rotavirus, Gujarat, Homoeopathy, LM Potency